Transformation of Digital Leadership Paradigms in Mitigating Operational Risks and Accelerating Labor Productivity within the Financial Services Sector - Afita, Anida Nur (CV. HEI PUBLISHING INDONESIA, 2025)
The rapid integration of exponential technologies within the financial services sector necessitates a fundamental re-evaluation of leadership approaches to ensure institutional resilience. This study investigates the transformation of digital leadership paradigms as a primary driver for mitigating operational risks and accelerating labor productivity using secondary data obtained from the Financial Services Authority (OJK) and Statistics Indonesia (BPS). A quantitative–descriptive approach was employed, involving correlation and regression analyses of 106 commercial banks during the period 2021–2024. The analysis evaluates the relationship between managerial digital strength and operational efficiency, measured by the Operational Costs to Operational Income (BOPO) ratio. The results indicate that institutions adopting advanced digital leadership strategies achieved a substantial reduction in BOPO ratios to 61.40% and a 21.40% decrease in operational losses attributable to human error. Furthermore, labor productivity, proxied by profit per employee, increased by 48.42% following the implementation of data-driven governance. These findings confirm that digital leadership plays a decisive role in transforming technological investments into sustainable competitive advantages. The study contributes to the literature by demonstrating that effective human–machine collaboration, guided by agile managerial practices, can successfully address the productivity paradox in contemporary banking.